Impact of Business Development Services on Performance of Micro-enterprises: Evidence from Field Survey in Kavreplanchok, Nepal - Neupane, Rabindra Kumar; Basnet, Bhupindra Jung (NPRC Journal of Multidisciplinary Research, 2025)
This article reveals the relationship between Business Development Services (BDS) and micro-enterprise performance based on the survey undertaken in Kavrepalanchok District of Nepal.  The survey was undertaken for the completion of Ph. D. dissertation on Business Development Services (BDS) for Enterprise Promotion in Nepal. The objective of this article is to analyze the relationship between the different components of BDS with enterprise performance development. The primary nature of data is used in this article collected from the field survey of micro-entrepreneurs at Kavrepalanchok District. A quantitative approach is used in this research. The population of this study is all the micro-entrepreneurs created in the Kavrepalanchok District by Business Development Service program of the Ministry of Industry, Nepal. The collected survey data has been analyzed using both descriptive and inferential statistical analysis techniques to examine the relationship between dependent and independent variables. Survey finding concluded that BDS components have a significant impact for improving performance of micro-enterprises having more than 90 per cent variability explained by BDS in the enterprise performance. This article contributes to lessen the dearth of publications in this topic in Nepal. Findings of this research will be useful to policy makers working in industry and enterprise development, management students, would-be entrepreneurs, and training and enterprise development service providers of Nepal.